Magnetic properties of quenched binary and ternary quasicrystal approximants - Fernand Denoel; Takayuki Shiino; Yu-Chin Huang; Girma Hailu Gebresenbut; Cesar Pay Gómez; Roland Mathieu (Scientific Reports)
Abstract The magnetic properties of binary Gd-Cd and ternary Gd-Au-Ge crystals obtained from the newly introduced low-melt peritectic formation (LMPF) synthesis method were investigated. This method consists of a rapid quenching of the metallic melt followed by an annealing treatment at a relevant temperature. In the first system, both quasicrystal (QC) and approximant crystal (AC) phases can be stabilized, whereas only the AC phase is obtainable in the pseudo-binary Gd-(Au-Ge) system. The magnetic properties of the crystals obtained from LMPF for each system are compared to those of larger single grain crystals obtained from the self-flux (SF) method.